Campur Kode Tuturan Komunitas Mahasiswa Mentawai Dalam Komunikasi Sehari-Hari Di Kota Padang - Susi Susanti; Asri Wahyuni Sari; Ria Satini (CV. Multi Kreasi Media, 2022)
This research is motivated by the tendency of studens to use Indonesian as adaily communication tool compared to unified languange or Indonesian. This study aims to first describe the types of code mixing contained in the speech of the Mentawai student community in daily communication in the city of Padang. This type of research is a qualitative description method. The data source of this research is ten students of Mentawai, the data of this research are the speeches of the Mentawai students in the form of moxing in code and mixing exit code. The data were analyzed by transcribing the data in written form. The second identifies data in the form of student routines in daily communication who experience code mixing. Third, classify data based on the type of code mixing and the form of code mx. Fourth, analyze and discuss data on research findings, fifth conclude the results of research findings. Based on the results of the study, it was found that code mixing was in the form of mixing in types of mixing code out, the forms of code mixing found were words, phrases and clauses code mixing is done by students how to approach other students who have the same mother tongue.